Religious Moderation Education for Students: How Should Teachers Respond? - Hodiqotul Atfaliyah; Yosie Kristin Pandriyani; Ali Muhtarom; Ahmad Qurtuby (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2025)
This study aims to describe the implementation of religious moderation in Islamic Religious Education at the junior high school level in two schools in Indonesia. Religious moderation as an educational approach is crucial in the context of Indonesia’s diverse society; therefore, schools play a strategic role in instilling values of tolerance, balance, and non-violence in students. This study employs a qualitative method with data collection techniques including observation, interviews with Islamic Religious Education teachers, and document analysis at the two schools. The findings indicate that Islamic Religious Education teachers at both schools have integrated the values of religious moderation through dialogue-based learning, modeling moderate behavior, selecting inclusive instructional materials, and fostering tolerant attitudes in school religious activities. Additionally, collaborative learning strategies and character-building activities helped students understand the meaning of religious moderation in a contextual manner. However, several challenges were identified, such as limited teacher training, differences in students’ backgrounds, and a lack of sustained school program support. This study recommends the need to enhance teachers’ competencies and develop more structured religious moderation programs within the school environment.